2020
DOI: 10.1186/s13643-020-01482-8
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of patient prioritization tools in non-emergency healthcare services

Abstract: Background Patient prioritization is a strategy used to manage access to healthcare services. Patient prioritization tools (PPT) contribute to supporting the prioritization decision process, and to its transparency and fairness. Patient prioritization tools can take various forms and are highly dependent on the particular context of application. Consequently, the sets of criteria change from one context to another, especially when used in non-emergency settings. This paper systematically synthe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 60 publications
0
25
0
2
Order By: Relevance
“…The reliability of specialist mental health care’s triage based on referral information, and the risk of under- and overestimation, as found in the current study, have been debated for many years [ 9 , 10 ]. Under- or overestimation of the urgency of patients’ need when decisions are based on referral information has been highlighted previously [ 9 , 10 ] and measures to improve reliability of triage decisions have been implemented [ 11 ]. In a similar setting to the present study, Holman and colleagues reported low interrater reliability for priority setting between local mental health centres, using vignettes of referral letters [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reliability of specialist mental health care’s triage based on referral information, and the risk of under- and overestimation, as found in the current study, have been debated for many years [ 9 , 10 ]. Under- or overestimation of the urgency of patients’ need when decisions are based on referral information has been highlighted previously [ 9 , 10 ] and measures to improve reliability of triage decisions have been implemented [ 11 ]. In a similar setting to the present study, Holman and colleagues reported low interrater reliability for priority setting between local mental health centres, using vignettes of referral letters [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Standardising triage decisions has been deemed necessary for correct assessment of treatment need [ 10 ]. Context-specific tools have been developed for assessing the urgency of treatment need to improve patient prioritisation [ 11 ]. A recent review of patient prioritisation tools for elective care indicated that 50% of the prioritisation tools that had been tested for reliability were categorised as acceptable to good [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The RE-AIM (reach, effectiveness, adoption, implementation, and maintenance) framework was used to guide evaluation of the knowledge translation strategy (18). Data were collected from two sources to inform each of the elements ( Table 1): (1) internally collected data from workshop attendance lists and CoP mailing list; (2) a cross-sectional survey of participants in the workshop series and service providers who requested to join the CoP mailing list. All participants who attended the workshops and people on the CoP mailing list were sent an email with an invitation to complete a short online survey.…”
Section: Evaluation Design and Data Sourcesmentioning
confidence: 99%
“…1(p4) Long waiting times are one of the main barriers to access experienced by patients in different health care sectors, including medical and paramedical services. 2,3 In health care, the concept of waiting can be expressed in different ways, but is most commonly measured as the time elapsed between referral for a service and first appointment. 4,5…”
Section: Introductionmentioning
confidence: 99%
“…1(p4) Long waiting times are one of the main barriers to access experienced by patients in different health care sectors, including medical and paramedical services. 2,3 In health care, the concept of waiting can be expressed in different ways, but is most commonly measured as the time elapsed between referral for a service and first appointment. 4,5 Findings to date have highlighted major gaps and disparities in access to publicly funded outpatient rehabilitation services in several countries, such as Canada, the United Kingdom (UK) and Australia.…”
Section: Introductionmentioning
confidence: 99%